Polyamide resin composition containing specific carboxylic acid-containing resin
By using a linear structure of new hydroxy acid-containing resin and ethylene acetate copolymer, combined with a rotary metal catalyst and thermal acid treatment technology, the problem of insufficient low-temperature impact resistance of polyamide resin is solved, and the effect of high efficiency, environmental protection and low-cost resin improvement is achieved.
Patent Information
- Application Number
- JP2021049834
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-03-24
AI Technical Summary
In the prior art, there are shortcomings in improving the impact resistance and low-temperature impact resistance of polyamide resins, especially when there is no metal ions, cost and environmental impact also become problems.
Using a novel hydroxy acid-containing resin with a linear molecular structure, a copolymer of ethylene and t-butyrate is polymerized using a rotary metal catalyst and converted into an ethylene acetate copolymer by heat or acid treatment, and then reacted with metal ions to form a binary ion resin.
The excellent low-temperature impact resistance and environmental protection performance of polyamide resin are achieved, and the pollution of metal ions and the increase in production costs are avoided.
Smart Images

Figure 0007666052000016 
Figure 0007666052000017 
Figure 0007666052000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyamide resin composition containing a novel carboxylic acid-containing resin. [Background technology]
[0002] Polyamide resins are widely used in automobile parts, exterior parts, machine parts, electric and electronic parts, etc., because of their excellent mechanical properties, heat resistance, electrical properties, moldability, etc. These parts are molded into a wide variety of shapes and used for various applications and environments, but polyamide resins inherently have low impact resistance, making them difficult to deploy in applications requiring toughness.
[0003] In an attempt to improve the impact resistance of polyamide resins, studies have been made on the inclusion of ionomer resins as modifiers in polyamide resins. For example, Patent Document 1 proposes an intimate mixture of 50-95% by weight of polyamide and 5-50% by weight of ethylene-based ionomer resin and / or carboxy-modified nitrile rubber. As another example, Patent Document 2 proposes a thermoplastic resin composition containing 5-100 parts by weight of a polyamide resin having a specific melting point for 100 parts by weight of a polyolefin-based thermoplastic resin having a crosslinked structure by metal ions between molecules and / or within molecules. Patent Document 3 proposes that a certain proportion of ionomer is blended with a specific polyamide to improve the moldability of the polyamide. In these patent documents, ionomers that are generally commercially available are used for the purpose of modifying the physical properties such as the impact resistance of polyamide resins.
[0004] Ionomers are synthetic resins in which polymers are aggregated with metal ions, and ethylene-based ionomers, which are resins in which an ethylene-unsaturated carboxylic acid copolymer is used as a precursor resin and intermolecularly bonded with metal ions such as sodium or zinc, are known (Patent Document 4). Ethylene-based ionomers are strong, elastic, and flexible, and have characteristics such as abrasion resistance and transparency. Currently, commercially available ethylene-based ionomers include "Surlyn (registered trademark)", a sodium salt or zinc salt of ethylene-methacrylic acid copolymer developed by Dupont, and "Himilan (registered trademark)" sold by Dow Mitsui Polychemicals.
[0005] However, the ethylene-unsaturated carboxylic acid copolymers, which are precursor resins used in these commercially available ethylene-based ionomers, all use polar group-containing olefin copolymers obtained by polymerizing ethylene and polar group-containing monomers such as unsaturated carboxylic acids by high-pressure radical polymerization. The high-pressure radical polymerization method has the advantage that it is possible to polymerize relatively any type of polar group-containing monomer at low cost. However, the molecular structure of the polar group-containing olefin copolymer produced by this high-pressure radical polymerization method has many irregular long chain branches and short chain branches, as shown in the image diagram in Figure 1, and has the disadvantage of insufficient strength.
[0006] In order to improve the shortcomings of polar group-containing olefin copolymers obtained by high-pressure radical polymerization, methods have been explored for polymerizing polar group-containing olefin copolymers with linear molecular structures, such as the image shown in Figure 2, using a catalyst. However, polar group-containing monomers are generally catalyst poisons, making it difficult to polymerize using a catalyst. Therefore, it has been difficult to obtain polar group-containing olefin copolymers with the desired physical properties using an industrially inexpensive and stable method. However, in recent years, the applicants of the present application have proposed a method for industrially producing polar group-containing olefin copolymers having a substantially linear molecular structure inexpensively and stably by using a new catalyst and a new production method. The applicants of the present application have reported that they have succeeded in producing a copolymer of ethylene and t-butyl acrylate using a late transition metal catalyst as a production method for a polar group-containing olefin copolymer that serves as a precursor resin for an ethylene-based ionomer, and modifying the resulting polar group-containing olefin copolymer by heat or acid treatment to form an ethylene-acrylic acid copolymer, which is then reacted with metal ions to produce a binary ionomer (Patent Document 5).
[0007] It has also been reported that a polyamide resin composition with improved impact resistance was obtained by using a novel ionomer made from this polar group-containing olefin copolymer having a substantially linear molecular structure (Patent Document 6). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Special Publication No. 55-41659 [Patent Document 2] JP 2015-163692 A [Patent Document 3] JP 2007-204674 A [Patent Document 4] U.S. Pat. No. 3,264,272 [Patent Document 5] JP 2016-79408 A [Patent Document 6] JP 2020-169318 A Summary of the Invention [Problem to be solved by the invention]
[0009] Various attempts have been made to modify polyamide, but the ionomers described in Patent Documents 1 to 3 are produced by high-pressure radical polymerization and have a structure with many long-chain branches and short-chain branches irregularly, so that their strength is insufficient. The ionomer itself, which is a modifier, has strength problems and is not sufficient in improving the impact resistance of polyamide resin compositions. In particular, Patent Document 3 has been found to be effective only for polyamides in a specific formulation, and is insufficient in terms of imparting physical properties based on the ionomer.
[0010] In addition, in Patent Document 6, an impact tensile test is performed at room temperature as a performance evaluation, and this test method is different from the impact bending test (Izod impact test, Charpy impact test) that is generally used as industrial data. Since the impact tensile test and the impact bending test have different fracture modes, even if an excellent result is obtained in the impact tensile test, it does not necessarily mean that a good result is obtained in the impact bending test. In addition, when evaluating impact resistance, it is also important that the cold impact resistance at low temperatures is good, taking into consideration the use of the product in cold regions. However, Patent Document 6 discloses improvements at room temperature, but does not mention cold impact resistance at low temperatures at all. Furthermore, Patent Document 6 discloses an experimental example in which a carboxylic acid-containing resin is used instead of an ionomer, but discloses that the impact strength value is lower than when an ionomer is used.
[0011] Although there have been reports of the impact resistance improvement of polyamide resin compositions using ionomers, the use of ionomers has the following concerns. First, since ionomers contain metal ions, polyamide resin compositions containing ionomers may be undesirable from an environmental perspective in terms of recycling and disposal. Second, since ionomers contain metal ions and there is a risk of metal ion elution, they may not be usable depending on the intended use. Third, ionomers are special synthetic resins in which polymers are aggregated by the effect of metal ions, and there is also the problem that they are expensive compared to general resins.
[0012] In view of the above-mentioned state of the art, the present invention aims to provide a modifier different from an ionomer that can give a polyamide resin having excellent cold impact resistance at low temperatures, and a polyamide resin composition having improved cold impact resistance by blending the modifier, at a lower cost. [Means for solving the problem]
[0013] As a result of extensive investigations by the present inventors to solve the above problems, it was found that the use of a specific carboxylic acid-containing resin has an excellent effect on the cold impact resistance of a polyamide-containing resin. The carboxylic acid-containing resin, which is a precursor resin of an ethylene-based ionomer as described in Patent Document 5, is a novel carboxylic acid-containing resin that has a substantially linear molecular structure and has not been seen before. Its physical properties, etc., are significantly different from those of conventional carboxylic acid-containing resins, and its unique characteristics and suitable applications were also unknown. The present invention is based on the discovery that a substantially linear novel carboxylic acid-containing resin unexpectedly has an excellent effect on improving the cold impact resistance of a polyamide resin.
[0014] That is, the present invention relates to a polyamide resin composition containing a polyamide resin (I) and a carboxylic acid-containing resin (II), in which the carboxylic acid-containing resin (II) is a copolymer containing, as essential constituent units, a structural unit (A) derived from ethylene and / or an α-olefin having 3 to 20 carbon atoms and a structural unit (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and the absolute value G of the complex modulus measured by a rotational rheometer is * The polyamide resin composition is characterized in that the phase angle δ at a compressive strength of 0.1 MPa is 50 degrees to 75 degrees. Effect of the Invention
[0015] According to the present invention, it is possible to provide a polyamide resin composition that has excellent cold impact resistance and is free of metal ions at low cost. The polyamide resin composition of the present invention, which contains the carboxylic acid-containing resin of the present invention that has a substantially linear structure, is excellent in cold impact resistance at low temperatures compared to conventional polyamide resin compositions, and is therefore useful as a material that requires toughness at low temperatures. In addition, the polyamide resin composition of the present invention is not only excellent in cold resistance, but also excellent in terms of the environment because it does not contain metal ions, and there is no risk of metal ion elution. Furthermore, since the process of producing an ionomer from a carboxylic acid-containing resin is not required, it is possible to reduce costs accordingly, and is also greatly excellent in terms of economy. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic diagram showing the molecular structure of a polar group-containing olefin copolymer produced by high-pressure radical polymerization. [Diagram 2] FIG. 2 is a schematic diagram showing the molecular structure of a polar group-containing olefin copolymer obtained by polymerization in the presence of a catalyst. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention relates to a polyamide resin composition that contains, as essential constituent units, structural units (A) derived from ethylene and / or an α-olefin having 3 to 20 carbon atoms and structural units (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and that uses a copolymer in which these are copolymerized substantially linearly, preferably randomly copolymerized, as a modifier.
[0018] The polyamide resin composition containing the carboxylic acid-containing resin according to the present invention and its applications will be described in detail below. In this specification, "(meth)acrylic acid" means acrylic acid or methacrylic acid. In this specification, "to" indicating a numerical range is used to mean that the numerical values before and after the range are included as the lower and upper limits.
[0019] 1. Polyamide resin (I) Polyamide resins are polymers having amide bonds in the molecular chain, which can be obtained, for example, by ring-opening polymerization of lactams having three or more ring members, polycondensation of aminocarboxylic acids, or polycondensation of dicarboxylic acids and diamines. Specific examples of lactams used in ring-opening polymerization include ε-caprolactam, enantholactam, and lauryllactam. Specific examples of aminocarboxylic acids used in polycondensation include 6-aminocaproic acid, 7-aminoheptanoic acid, 8-aminooctanoic acid, 9-aminononanoic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid. Specific examples of monomers used in the polycondensation of dicarboxylic acids and diamines include any combination of diamines such as 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,5-hexanediamine, 1,9-nonanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, α,ω-diaminopolypropylene glycol, m- or p-phenylenediamine, and dicarboxylic acids such as adipic acid, sebacic acid, dodecanedioic acid, glutaric acid, terephthalic acid, and isophthalic acid. The polyamide resin may be a copolymer obtained from a plurality of different monomers (for example, Toray Industries, Inc., product name: Amilan (registered trademark), grade: CM6246M (6-nylon / 6,6-nylon copolymer), etc.), and homopolymers or copolymers may be blended in any ratio.
[0020] As the polyamide resin, commercially available grades can be used, but more preferred specific examples of polyamides include 6-nylon, 6,6-nylon, 6,10-nylon, 12-nylon, 11-nylon, 9-nylon, 7-nylon, polyamide 4,6, polyamide 6,12, polymetaxylylene adipamide, aromatic nylons such as polyamide 6T, polyamide 9T, and polyamide 10T. These can be used alone or in combination of two or more. Among these, preferred are 6-nylon, 6,6-nylon, 6,10-nylon, 12-nylon, and 11-nylon, more preferred are 6-nylon, 12-nylon, and 11-nylon, and particularly preferred is 6-nylon.
[0021] The ends of these polyamide resins may be blocked with a carboxylic acid or amine having 6 to 22 carbon atoms. Specific examples of the carboxylic acid used for blocking include aliphatic monocarboxylic acids such as caproic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, and behenic acid. Examples of the amine include aliphatic primary amines such as hexylamine, octylamine, decylamine, laurylamine, myristylamine, palmitylamine, stearylamine, and behenylamine.
[0022] The polyamide resin can be adjusted to some extent freely depending on the specific application, but it is preferable that the molecular weight is within a certain range. The length of the molecular chain, i.e., the molecular weight, of a polymer can also be expressed by the relative viscosity (ηr). The preferred relative viscosity of the polyamide resin is in the range of 1.5 to 5.0, more preferably 2.0 to 5.0, as measured in 98% sulfuric acid at a resin concentration of 1% and at a temperature of 25°C according to JIS K6810.
[0023] The amount of polyamide resin in the resin composition is more than 80 and 99.9% by weight or less based on the total amount including the carboxylic acid-containing resin described below. It is more preferably in the range of 85 to 99.0% by weight, more preferably in the range of 90 to 99.0% by weight or in the range of 85 to 95% by weight, and particularly preferably in the range of 90 to 95% by weight based on the total amount including the carboxylic acid-containing resin. By setting it in this range, it is possible to obtain a polyamide resin composition that satisfies the required physical properties such as moldability as a resin and has excellent cold impact resistance.
[0024] 2. Carboxylic acid-containing resin (II) The carboxylic acid-containing resin of the present invention is characterized in that it contains, as essential constituent units, structural units (A) derived from ethylene and / or an α-olefin having 3 to 20 carbon atoms and structural units (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and is a copolymer in which these are substantially copolymerized in a linear fashion, preferably randomly copolymerized. Here, "containing carboxylic acid" means having a carboxyl group and / or a dicarboxylic anhydride group, and the carboxyl group is not particularly neutralized with a metal ion.
[0025] (1) Structural unit (A) The structural unit (A) is at least one structural unit selected from the group consisting of structural units derived from ethylene and structural units derived from an α-olefin having 3 to 20 carbon atoms. The α-olefins involved in the present invention have the structural formula: CH2=CHR 18 is an α-olefin having 3 to 20 carbon atoms (R 18 is a hydrocarbon group having 1 to 18 carbon atoms, which may have a linear structure or may be branched.) The α-olefin more preferably has 3 to 12 carbon atoms.
[0026] Specific examples of the structural unit (A) include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 3-methyl-1-butene, and 4-methyl-1-pentene, and may be ethylene. The structural unit (A) contained in the carboxylic acid-containing resin may be one type or multiple types. Examples of combinations of two types include ethylene-propylene, ethylene-1-butene, ethylene-1-hexene, ethylene-1-octene, propylene-1-butene, propylene-1-hexene, and propylene-1-octene. Examples of combinations of three types include ethylene-propylene-1-butene, ethylene-propylene-1-hexene, ethylene-propylene-1-octene, propylene-1-butene-hexene, and propylene-1-butene-1-octene.
[0027] In the present invention, the structural unit (A) preferably contains ethylene as an essential component and may further contain one or more α-olefins having 3 to 20 carbon atoms, if necessary. The amount of ethylene in the structural unit (A) may be 65 to 100 mol % or 70 to 100 mol % based on the total moles of the structural unit (A).
[0028] (2) Structural unit (B) The structural unit (B) is a structural unit derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group.
[0029] Specific examples of monomers having a carboxyl group include unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, norbornene dicarboxylic acid, and bicyclo[2.2.1]hept-2-ene-5,6-dicarboxylic acid. Examples of monomers having a dicarboxylic acid anhydride group include maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, 3,6-epoxy-1,2,3,6-tetrahydrophthalic anhydride, and tetracyclo[6.2.1.1 3,6 .0 2,7 ] Unsaturated dicarboxylic acid anhydrides such as dodec-9-ene-4,5-dicarboxylic acid anhydride and 2,7-octadien-1-yl succinic acid anhydride are exemplified. Specific compounds include acrylic acid, methacrylic acid, 5-norbornene-2,3-dicarboxylic anhydride, and in particular acrylic acid. Furthermore, the monomer having a carboxyl group and / or a dicarboxylic anhydride group may be of one type or of multiple types.
[0030] In addition, the dicarboxylic anhydride group may react with moisture in the air to open the ring and become a part of the dicarboxylic acid, but the dicarboxylic anhydride group may be in a ring-opened state as long as it does not deviate from the gist of the present invention.
[0031] (3) Other structural units (C) The copolymer according to the present invention may contain a structural unit (C) other than the structural units represented by the structural units (A) and (B) (hereinafter, may be referred to as "any monomer (C)"). Any monomer can be used as the monomer that gives the structural unit (C) as long as it is not the same as the monomer that gives the structural unit (A) and the structural unit (B). Preferably, the monomer does not contain a metal element that can become a cation. The any monomer that gives the structural unit (C) is not limited as long as it is a compound having one or more carbon-carbon double bonds in the molecular structure, and examples thereof include acyclic monomers represented by the following general formula (1) and cyclic monomers represented by the following general formula (2).
[0032] Acyclic Monomers [ka] [In general formula (1), T 1 ~T 3 each independently represents a substituent selected from the group consisting of a hydrogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a hydrocarbon group having 1 to 20 carbon atoms substituted with a hydroxyl group, a hydrocarbon group having 2 to 20 carbon atoms substituted with an alkoxy group having 1 to 20 carbon atoms, a hydrocarbon group having 3 to 20 carbon atoms substituted with an ester group having 2 to 20 carbon atoms, a hydrocarbon group having 1 to 20 carbon atoms substituted with a halogen atom, an alkoxy group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an ester group having 2 to 20 carbon atoms, a silyl group having 3 to 20 carbon atoms, a halogen atom, or a cyano group; T 4 is a substituent selected from the group consisting of a hydrocarbon group having 1 to 20 carbon atoms substituted with a hydroxyl group, a hydrocarbon group having 2 to 20 carbon atoms substituted with an alkoxy group having 1 to 20 carbon atoms, a hydrocarbon group having 3 to 20 carbon atoms substituted with an ester group having 2 to 20 carbon atoms, a hydrocarbon group having 1 to 20 carbon atoms substituted with a halogen atom, an alkoxy group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an ester group having 2 to 20 carbon atoms, a silyl group having 3 to 20 carbon atoms, a halogen atom, or a cyano group.
[0033] In the copolymer of the present invention, T 1 and T 2 may be a hydrogen atom, T 3 may be a hydrogen atom or a methyl group, T 4 may be an ester group having 2 to 20 carbon atoms.
[0034] T 1 ~T 4 The carbon skeleton of the hydrocarbon group, substituted alkoxy group, substituted ester group, alkoxy group, aryl group, ester group and silyl group may have a branch, a ring, and / or an unsaturated bond. T 1 ~T 4 The lower limit of the number of carbon atoms in the hydrocarbon group may be 1 or more, and the upper limit may be 20 or less, or may be 10 or less. T 1 ~T 4 The lower limit of the number of carbon atoms in the substituted alkoxy group may be 1 or more, and the upper limit may be 20 or less, or may be 10 or less. T 1 ~T 4 The lower limit of the number of carbon atoms in the substituted ester group may be 2 or more, and the upper limit may be 20 or less, or may be 10 or less. T 1 ~T 4 The lower limit of the number of carbon atoms in the alkoxy group may be 1 or more, and the upper limit may be 20 or less, or may be 10 or less. T 1 ~T 4 The lower limit of the number of carbon atoms in the aryl group in the above formula may be 6 or more, and the upper limit may be 20 or less, or may be 11 or less. T 1 ~T 4 The lower limit of the number of carbon atoms in the ester group may be 2 or more, and the upper limit may be 20 or less, or may be 10 or less. T 1 ~T 4The number of carbon atoms in the silyl group in the above formula may be 3 or more, and may be 18 or less, or may be 12 or less. Examples of the silyl group include a trimethylsilyl group, a triethylsilyl group, a tri-n-propylsilyl group, a triisopropylsilyl group, a dimethylphenylsilyl group, a methyldiphenylsilyl group, and a triphenylsilyl group.
[0035] Specific examples of the acyclic monomer include (meth)acrylic acid esters. The (meth)acrylic acid ester according to the present invention has the structural formula: CH2=C(R 21 )CO2(R 22 ) where R 21 R is a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms, which may have a branch, a ring, and / or an unsaturated bond. 22 is a hydrocarbon group having 1 to 20 carbon atoms, which may have a branch, a ring, and / or an unsaturated bond. 22 It may contain a heteroatom at any position within the group. As the (meth)acrylic acid ester, R 21 is a (meth)acrylic acid ester which is a hydrogen atom or a hydrocarbon group having 1 to 5 carbon atoms. 21 is a hydrogen atom, or R 21 Methacrylate esters in which the alkyl group is a methyl group are also included. Specific examples of (meth)acrylic acid esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, octadecyl (meth)acrylate, phenyl (meth)acrylate, toluyl (meth)acrylate, and benzyl (meth)acrylate. Specific compounds include methyl acrylate, ethyl acrylate, n-butyl acrylate (nBA), isobutyl acrylate (iBA), t-butyl acrylate (tBA), and 2-ethylhexyl acrylate, and may in particular be n-butyl acrylate (nBA), isobutyl acrylate (iBA), and t-butyl acrylate (tBA). The non-cyclic monomer may be used alone or in combination of two or more kinds.
[0036] Cyclic Monomers [ka] [In general formula (2), R 1 ~R 12 may be the same or different and are selected from the group consisting of a hydrogen atom, a halogen atom, and a hydrocarbon group having 1 to 20 carbon atoms; R 9 and R 10 , and R 11 and R 12 may combine together to form a divalent organic group, R 9 or R 10 And, R 11 or R 12 may form a ring together. In addition, n represents 0 or a positive integer, and when n is 2 or more, R 5 ~R 8 may be the same or different in each repeating unit.
[0037] Examples of the cyclic monomer include norbornene-based olefins, such as norbornene, vinylnorbornene, ethylidenenorbornene, norbornadiene, tetracyclododecene, tricyclo[4.3.0.1 2,5 ]dec-1-ene, tricyclo[4.3.0.1 2,5 ]dec-3-ene, and other compounds having a cyclic olefin skeleton. 3,6 .0 2,7]dodec-4-ene and the like.
[0038] (4) Copolymer The copolymer used in the present invention is characterized in that it contains, as essential constituent units, structural units (A) derived from ethylene and / or an α-olefin having 3 to 20 carbon atoms and structural units (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, which are copolymerized substantially linearly, preferably randomly. "Substantially linear" refers to a state in which the copolymer has no branch or the frequency of branched structures appearing is low, and the copolymer can be considered to be linear. Specifically, it refers to a state in which the phase angle δ of the copolymer measured under the following conditions is 50 degrees or more.
[0039] The copolymer according to the present invention must contain at least one type of structural unit (A) and at least one type of structural unit (B), that is, at least two types of monomer units in total, and may also contain another structural unit (C). The structural units and the amounts of the structural units in the copolymer according to the present invention will be described below. A structure derived from one molecule each of ethylene and / or an α-olefin having 3 to 20 carbon atoms (A), a monomer having a carboxyl group and / or a dicarboxylic anhydride group (B), and an arbitrary monomer (C) is defined as one structural unit in the copolymer. The amount of structural units is the ratio of each structural unit expressed in mol % when all structural units in the copolymer are taken as 100 mol %.
[0040] Amount of structural units of ethylene and / or α-olefin having 3 to 20 carbon atoms (A): The structural unit amount of the structural unit (A) according to the present invention is selected from the following: lower limit is 60.000 mol% or more, preferably 70.000 mol% or more, more preferably 80.000 mol% or more, even more preferably 85.000 mol% or more, even more preferably 90.000 mol% or more, and particularly preferably 91.200 mol% or more; and upper limit is 97.999 mol% or less, preferably 97.990 mol% or less, more preferably 97.980 mol% or less, even more preferably 96.980 mol% or less, even more preferably 96.900 mol% or less, and particularly preferably 92.700 mol% or less. If the amount of structural units derived from ethylene and / or the α-olefin (A) having 3 to 20 carbon atoms is less than 60,000 mol%, the rigidity of the polyamide resin composition may be inferior, and if it is more than 97.999 mol%, the improving effect of the polyamide resin composition may be reduced.
[0041] Amount of structural units derived from monomer (B) having a carboxyl group and / or a dicarboxylic anhydride group: The amount of the structural unit (B) according to the present invention is selected from the following: the lower limit is 2.0 mol% or more, preferably 2.9 mol% or more, and more preferably 5.2 mol% or more, and the upper limit is 20.0 mol% or less, preferably 15.0 mol% or less, more preferably 10.0 mol% or less, even more preferably 8.0 mol% or less, and particularly preferably 5.4 mol% or less. If the amount of structural units derived from the monomer (B) having a carboxyl group and / or a dicarboxylic anhydride group is less than 2.0 mol%, the effect of improving the impact resistance of the copolymer with respect to the polyamide resin is impaired, and if it exceeds 20.0 mol%, the polyamide resin composition may not have sufficient mechanical properties.
[0042] Amount of structural units of any monomer (C): The amount of the structural unit (C) according to the present invention, when the structural unit (C) is contained, is selected from the following: the lower limit is 0.001 mol% or more, preferably 0.010 mol% or more, more preferably 0.020 mol% or more, even more preferably 0.100 mol% or more, still more preferably 1.000 mol% or more, and particularly preferably 1.900 mol% or more, and the upper limit is 20.000 mol% or less, preferably 15.000 mol% or less, more preferably 10.000 mol% or less, even more preferably 5.000 mol% or less, and particularly preferably 3.600 mol% or less. Furthermore, any of the monomers used may be used alone or in combination of two or more kinds.
[0043] Number of branches per 1,000 carbons in copolymer: In the molecular structure of polyolefin, short carbon chains having about 1 to 4 carbon atoms, such as methyl, ethyl, and butyl, may appear as branches. The copolymer of the present invention has no branches or only a small frequency of branched structures, and has a structure that can be considered as linear. In the case of copolymers, in order to increase the elastic modulus and obtain sufficient mechanical properties, 13 The number of methyl branches calculated by C-NMR may be 50 or less, 5.0 or less, 1.0 or less, or 0.5 or less per 1,000 carbons. The lower limit of the number of methyl branches is not particularly limited, and the lower the better. The number of ethyl branches may be 3.0 or less, 2.0 or less, 1.0 or less, or 0.5 or less per 1,000 carbons. The lower limit of the number of ethyl branches is not particularly limited, and the lower the better. The number of butyl branches may be 7.0 or less, 5.0 or less, 3.0 or less, or 0.5 or less per 1,000 carbons. The lower limit of the number of butyl branches is not particularly limited, and the lower the better.
[0044] Method for measuring the number of structural units and branches derived from carboxyl and / or dicarboxylic anhydride monomers in copolymers: The number of branches per 1,000 carbon atoms of the structural units derived from carboxyl and / or dicarboxylic anhydride monomers in the multicomponent copolymer of the present invention is 13 It can be determined using C-NMR spectroscopy. 13 C-NMR is measured by the following method. 200-300 mg of sample is placed in an NMR sample tube with an inner diameter of 10 mm together with 2.4 ml of a mixed solvent of o-dichlorobenzene (C6H4Cl2) and deuterated bromide benzene (C6D5Br) (C6H4Cl2 / C6D5Br = 2 / 1 (volume ratio)) and hexamethyldisiloxane, a chemical shift standard substance, and the tube is sealed after replacing with nitrogen. It is heated and dissolved to prepare a homogeneous solution, which is used as the NMR measurement sample. NMR measurements are performed at 120°C using an AV400M NMR instrument from Bruker Japan Ltd. equipped with a 10 mmφ cryoprobe. 13 C-NMR was measured using the inverse gate decoupling method with a sample temperature of 120°C, a pulse angle of 90°, a pulse interval of 51.5 seconds, and an accumulation count of 512 or more. The chemical shifts are those of hexamethyldisiloxane. 13 The C signal was set to 1.98 ppm, and the other 13 The chemical shifts of the C signals are based on this. Obtained 13 In C-NMR, the amount of structural units of each monomer in the copolymer and the number of branches can be analyzed by identifying signals specific to the monomers or branches contained in the copolymer and comparing their intensities. The positions of signals specific to the monomers or branches can be referred to publicly known materials or can be independently identified depending on the sample. Such analytical techniques are commonly known to those skilled in the art.
[0045] Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn): The weight average molecular weight (Mw) of the copolymer according to the present invention has a lower limit of usually 1,000 or more, preferably 6,000 or more, and an upper limit of usually 2,000,000 or less, preferably 1,500,000 or less, more preferably 1,000,000 or less, particularly preferably 800,000 or less, and most preferably 56,000 or less. If the Mw is less than 1,000, the physical properties such as mechanical strength and impact resistance of the copolymer will be insufficient, whereas if the Mw exceeds 2,000,000, the melt viscosity of the copolymer will be extremely high, making it difficult to mold the copolymer.
[0046] The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the copolymer according to the present invention is usually in the range of 1.5 to 4.0, preferably 1.6 to 3.5, and more preferably 1.9 to 2.3. If Mw / Mn is less than 1.5, the copolymer may have insufficient processability, including molding, whereas if it exceeds 4.0, the copolymer may have poor mechanical properties. In the present invention, (Mw / Mn) may be expressed as a molecular weight distribution parameter.
[0047] The weight average molecular weight (Mw) and number average molecular weight (Mn) in the present invention are determined by gel permeation chromatography (GPC). The molecular weight distribution parameter (Mw / Mn) is determined by determining the number average molecular weight (Mn) by gel permeation chromatography (GPC) and calculating the ratio of Mw to Mn, Mw / Mn.
[0048] An example of the GPC measurement method according to the present invention is as follows. (Measurement conditions) Machine used: Waters 150C Detector: FOXBORO MIRAN1A IR detector (measurement wavelength: 3.42 μm) Measurement temperature: 140℃ Solvent: orthodichlorobenzene (ODCB) Column: Showa Denko AD806M / S (3 columns) Flow rate: 1.0mL / min Injection volume: 0.2mL (Sample preparation) A 1 mg / mL solution of the sample is prepared using ODCB (containing 0.5 mg / mL BHT (2,6-di-t-butyl-4-methylphenol)), and dissolved at 140° C. for about 1 hour. (Calculation of molecular weight (M)) The standard polystyrene method is used, and the conversion from retention volume to molecular weight is performed using a calibration curve prepared in advance using standard polystyrene. All of the standard polystyrenes used are Tosoh Corporation brands (F380, F288, F128, F80, F40, F20, F10, F4, F1, A5000, A2500, A1000). A calibration curve is created by injecting 0.2 mL of a solution in which each of the polystyrenes is dissolved in ODCB (containing 0.5 mg / mL BHT) so that the concentration is 0.5 mg / mL. The calibration curve uses a cubic equation obtained by approximating with the least squares method. The viscosity equation [η] = K × Mα used for conversion to molecular weight (M) uses the following values. Polystyrene (PS): K = 1.38 x 10 -4 , α=0.7 Polyethylene (PE): K = 3.92 x 10 -4 , α=0.733 Polypropylene (PP): K = 1.03 x 10 -4 , α=0.78
[0049] Melting point (Tm, ℃): The melting point of the copolymer according to the present invention is indicated by the maximum peak temperature of the endothermic curve measured by a differential scanning calorimeter (DSC). When multiple peaks are shown in the endothermic curve obtained by DSC measurement, with heat flow (mW) on the vertical axis and temperature (°C) on the horizontal axis, the maximum peak temperature refers to the temperature of the peak with the maximum height from the baseline among the multiple peaks, or when there is only one peak, the maximum peak temperature refers to the temperature of that peak. The melting point is preferably 50° C. to 140° C., more preferably 60° C. to 138° C., and most preferably 70° C. to 135° C. If it is lower than this range, the heat resistance is insufficient, and if it is higher than this range, the rigidity of the polyamide resin composition may be inferior. The melting point of the copolymer can be determined, for example, from the absorption curve obtained by using a DSC (DSC7020) manufactured by SII Nano Technology Inc., packing approximately 5.0 mg of a sample into an aluminum pan, heating the sample to 200°C at 10°C / min, holding the sample isothermally at 200°C for 5 minutes, lowering the sample to 20°C at 10°C / min, holding the sample isothermally at 20°C for 5 minutes, and then heating the sample again to 200°C at 10°C / min.
[0050] Crystallinity (%): In the copolymer of the present invention, the crystallinity observed by differential scanning calorimetry (DSC) is not particularly limited, but is preferably more than 0%. More preferably, it is more than 5%, and even more preferably 7% or more. If the crystallinity is 0%, the toughness of the copolymer may not be sufficient. In addition, the crystallinity is an index of transparency, and it can be judged that the lower the crystallinity of the copolymer, the more excellent its transparency. In applications requiring transparency, the crystallinity of the copolymer is preferably 30% or less, more preferably 25% or less, particularly preferably 25% or less, and most preferably 24% or less. The crystallinity of the copolymer can be determined, for example, by determining the heat of fusion (ΔH) from the area of the melting endothermic peak obtained by DSC measurement using the same procedure as in the measurement of the melting point, and dividing the heat of fusion by the heat of fusion of perfectly crystalline high-density polyethylene (HDPE), which is 293 J / g.
[0051] Molecular structure of copolymer: The molecular chain terminals of the copolymer according to the present invention may be structural units (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms, structural units (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group, or structural units (C) of any monomer.
[0052] The copolymer according to the present invention may be a random copolymer, block copolymer, graft copolymer, etc., of a structural unit (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms, a structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and a structural unit (C) of an arbitrary monomer. Among these, a random copolymer that can contain a large amount of the structural unit (B) may be used. An example of the molecular structure of a typical ternary copolymer (1) is shown below. A random copolymer is a copolymer in which the probability of finding a structural unit (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms, a structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and a structural unit (C) of an arbitrary monomer at a position in an arbitrary molecular chain, as shown in the molecular structure example (1) below, is independent of the type of the adjacent structural unit. As shown below, in the molecular structure example (1) of the copolymer, a structural unit (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms, a structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and a structural unit (C) of an arbitrary monomer form a random copolymer.
[0053] [ka]
[0054] For reference, an example of a molecular structure (2) of a copolymer into which structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group has been introduced by graft modification is shown. A part of a copolymer in which structural unit (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms and structural unit (C) of an arbitrary monomer are copolymerized is graft modified with structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group.
[0055] [ka]
[0056] In addition, the random copolymerization of a copolymer can be confirmed by various methods, but a method for determining the random copolymerization from the relationship between the comonomer content and melting point of the copolymer is described in detail in JP 2015-163691 A and JP 2016-079408 A. From the above documents, it can be determined that the randomness is low when the melting point (Tm, °C) of the copolymer is higher than -3.74 × [Z] + 130 (where [Z] is the comonomer content / mol%).
[0057] The copolymer according to the present invention, which is a random copolymer, preferably has a melting point (Tm, °C) measured by differential scanning calorimetry (DSC) and a total content [Z] (mol %) of the structural unit (B) of the monomer having a carboxyl group and / or a dicarboxylic anhydride group and the structural unit (C) of an arbitrary monomer, which satisfy the following formula (I): 50 <Tm<-3.74×[Z]+130···(I) If the melting point of the copolymer (Tm, °C) is higher than -3.74 × [Z] + 130 (°C), the random copolymerization is low, resulting in poor mechanical properties such as impact strength. If the melting point is lower than 50°C, the heat resistance may be poor.
[0058] Furthermore, the copolymer according to the present invention is preferably produced in the presence of a transition metal catalyst, from the viewpoint of making the molecular structure thereof linear. It is known that the molecular structure of the copolymer varies depending on the production method, such as polymerization by a high-pressure radical polymerization process or polymerization using a metal catalyst. The difference in molecular structure can be controlled by selecting the production method, but the molecular structure can also be estimated from the complex modulus measured with a rotational rheometer, as described in JP 2010-150532 A, for example.
[0059] · Absolute value of complex elastic modulus G * Phase angle δ at =0.1MPa: In the copolymer of the present invention, the absolute value of the complex modulus G measured by a rotational rheometer *= 0.1 MPa, the phase angle δ is 50 to 75 degrees. The lower limit of the phase angle δ may be 51 degrees or more, 54 degrees or more, 56 degrees or more, or 58 degrees or more. The upper limit of the phase angle δ may be 75 degrees or less, or 70 degrees or less. More specifically, the absolute value of the complex modulus G measured by a rotational rheometer * = Phase angle δ at 0.1 MPa (G * =0.1 MPa) is 50 degrees or more, the molecular structure of the copolymer is a linear structure containing no long chain branches or a substantially linear structure containing a small amount of long chain branches that does not affect the mechanical strength. In addition, the absolute value of the complex modulus G measured by a rotational rheometer * = Phase angle δ at 0.1 MPa (G * = 0.1 MPa) is lower than 50 degrees, the molecular structure of the copolymer will contain excessive long chain branches, resulting in poor mechanical strength. Absolute value of complex modulus G measured by a rotational rheometer * The phase angle δ at G = 0.1 MPa is affected by both the molecular weight distribution and long chain branching. However, for copolymers with Mw / Mn ≦ 4, more preferably Mw / Mn ≦ 3, it is an index of the amount of long chain branching, and the more long chain branches there are in the molecular structure, the lower the δ(G * If the Mw / Mn of the copolymer is 1.5 or more, the δ(G * =0.1MPa) value never exceeds 75 degrees.
[0060] The method for measuring the complex elastic modulus is as follows. The sample is placed in a 1.0 mm thick mold for hot pressing, preheated for 5 minutes in a hot press machine with a surface temperature of 180°C, and then the residual gas in the molten resin is degassed by repeatedly applying and depressurizing pressure, and then pressurized to 4.9 MPa and held for 5 minutes. The sample is then transferred to a press machine with a surface temperature of 25°C, and cooled by holding at a pressure of 4.9 MPa for 3 minutes to create a press plate with a thickness of approximately 1.0 mm. The press plate is processed into a circular shape with a diameter of 25 mm to serve as a sample, and a Rheometrics ARES type rotational rheometer is used to measure the dynamic viscoelastic properties under the following conditions in a nitrogen atmosphere. Plate: φ25mm parallel plate ·Temperature: 160℃ Distortion: 10% Measurement angular frequency range: 1.0×10 -2 ~1.0×10 2 rad / s Measurement interval: 5 points / decade Absolute value of complex elastic modulus G * Common logarithm logG of (Pa) * Plot the phase angle δ against logG * = 5.0, the value of δ (degrees) at the point * = 0.1MPa). * If there is no point corresponding to =5.0, logG * Using two points around =5.0, logG * The δ value at logG = 5.0 is calculated by linear interpolation. * <5, logG * Using the three largest values, we plot logG on a quadratic curve. * = 5.0.
[0061] - Copolymer production The copolymer according to the present invention is preferably produced in the presence of a transition metal catalyst, from the viewpoint of making the molecular structure thereof linear.
[0062] Polymerization catalyst The type of polymerization catalyst used in the production of the copolymer according to the present invention is not particularly limited as long as it is capable of copolymerizing the structural unit (A), the structural unit (B), and the optional structural unit (C). For example, a transition metal compound of Groups 5 to 11 having a chelating ligand can be mentioned. Specific examples of preferred transition metals include vanadium atom, niobium atom, tantalum atom, chromium atom, molybdenum atom, tungsten atom, manganese atom, iron atom, platinum atom, ruthenium atom, cobalt atom, rhodium atom, nickel atom, palladium atom, copper atom, etc. Among these, preferred are transition metals of Groups 8 to 11, more preferred are transition metals of Group 10, and particularly preferred are nickel (Ni) and palladium (Pd). These metals may be used alone or in combination. Chelating ligands have at least two atoms selected from the group consisting of P, N, O, and S, and include ligands that are bidentate or multidentate, and are electronically neutral or anionic. Exemplary chelating ligand structures are given in the review by Brookhart et al. (Chem. Rev., 2000, 100, 1169). The chelating ligand preferably includes a bidentate anionic P, O ligand. Examples of the bidentate anionic P, O ligand include phosphorus sulfonic acid, phosphorus carboxylic acid, phosphorus phenol, and phosphorus enolate. Other examples of the chelating ligand include a bidentate anionic N, O ligand. Examples of the bidentate anionic N, O ligand include salicylaldimine and pyridine carboxylic acid. Other examples of the chelating ligand include a diimine ligand, a diphenoxide ligand, and a diamide ligand.
[0063] The structure of the metal complex obtained from the chelating ligand is represented by the following structural formula (c1) or (c2) in which an arylphosphine compound, an arylarsine compound or an arylantimony compound which may have a substituent is coordinated.
[0064] [ka]
[0065] [ka]
[0066] [In structural formula (c1) and structural formula (c2), M represents a transition metal belonging to any of Groups 5 to 11 of the periodic table of the elements, that is, various transition metals as described above. X 1 represents oxygen, sulfur, -SO3-, or -CO2-. Y 1 represents carbon or silicon. n represents an integer of 0 or 1. E 1 represents phosphorus, arsenic or antimony. R 53 and R 54 each independently represents hydrogen or a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom. R 55 each independently represents hydrogen, halogen, or a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom. R 56 and R 57 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom, OR 52 , CO2R 52 , CO2M', C(O)N(R 51 )2, C(O)R 52 , S.R. 52 , SO2R 52 , SOR 52 , OSO2R 52 , P(O)(OR 52 ) 2-y (R 51 ) y , C.N., N.H.R. 52 , N(R 52 )2, Si(OR 51 ) 3-x (R 51 ) x , OSi(OR 51) 3-x (R 51 ) x , NO2, SO3M', PO3M'2, P(O)(OR 52 )2M' or an epoxy-containing group. R 51 represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms. R 52 represents a hydrocarbon group having 1 to 20 carbon atoms. M′ represents an alkali metal, an alkaline earth metal, ammonium, a quaternary ammonium or a phosphonium; x represents an integer of 0 to 3; and y represents an integer of 0 to 2. In addition, R 56 and R 57 may be linked to each other to form an alicyclic ring, an aromatic ring, or a heterocyclic ring containing a heteroatom selected from oxygen, nitrogen, or sulfur, in which case the ring has 5 to 8 members and may or may not have a substituent on the ring. L 1 represents a ligand coordinated to M. Also, R 53 and L 1 may be bonded to each other to form a ring.
[0067] More preferably, the complex serving as the polymerization catalyst is a transition metal complex represented by the following structural formula (c3).
[0068] [ka]
[0069] [In structural formula (c3), M represents a transition metal belonging to any of Groups 5 to 11 of the periodic table of the elements, that is, various transition metals as described above. X 1 represents oxygen, sulfur, -SO3-, or -CO2-. Y 1 represents carbon or silicon. n represents an integer of 0 or 1. E 1 represents phosphorus, arsenic or antimony. R 53 and R 54 each independently represents hydrogen or a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom. R 55 each independently represents hydrogen, halogen, or a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom. R 58 , R 59 , R 60 and R 61 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom, OR 52 , CO2R 52 , CO2M', C(O)N(R 51 )2, C(O)R 52 , S.R. 52 , SO2R 52 , SOR 52 , OSO2R 52 , P(O)(OR 52 ) 2-y (R 51 ) y , C.N., N.H.R. 52 , N(R 52 )2, Si(OR 51 ) 3-x (R 51 ) x , OSi(OR 51 ) 3-x (R 51 ) x , NO2, SO3M', PO3M'2, P(O)(OR 52 )2M' or an epoxy-containing group. R 51 represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms. R 52 represents a hydrocarbon group having 1 to 20 carbon atoms. M′ represents an alkali metal, an alkaline earth metal, ammonium, a quaternary ammonium or a phosphonium; x represents an integer of 0 to 3; and y represents an integer of 0 to 2. In addition, R 58 ~R 61may be bonded to each other to form an alicyclic ring, an aromatic ring, or a heterocyclic ring containing a heteroatom selected from oxygen, nitrogen, or sulfur. In this case, the number of ring members is 5 to 8, and the ring may or may not have a substituent. L 1 represents a ligand coordinated to M. Also, R 53 and L 1 may be bonded to each other to form a ring.
[0070] Here, typical catalysts of Group 5 to 11 transition metal compounds having a chelating ligand include so-called SHOP catalysts and Drent catalysts. The SHOP catalyst is a catalyst in which a phosphorus-based ligand having an aryl group which may have a substituent is coordinated to nickel metal (see, for example, WO2010-050256). Furthermore, the Drent catalyst is a catalyst in which a phosphorus-based ligand having an aryl group which may have a substituent is coordinated to palladium metal (see, for example, JP-A-2010-202647).
[0071] Copolymerization method: The polymerization method for the copolymer according to the present invention is not limited. Examples of the polymerization method include slurry polymerization in which at least a portion of the produced polymer becomes a slurry in a medium, bulk polymerization in which the liquefied monomer itself is used as the medium, gas phase polymerization in vaporized monomer, and high pressure ionic polymerization in which at least a portion of the produced polymer is dissolved in monomer liquefied at high temperature and pressure. The polymerization method may be any of batch polymerization, semi-batch polymerization, and continuous polymerization. Furthermore, living polymerization may be carried out, or polymerization may be carried out while simultaneously causing chain transfer. Furthermore, during polymerization, a so-called chain shuttling agent (CSA) may be used in combination to carry out a chain shuttling reaction or coordinate chain transfer polymerization (CCTP). Specific manufacturing processes and conditions are disclosed in, for example, Japanese Patent Application Laid-Open No. 2010-260913 and Japanese Patent Application Laid-Open No. 2010-202647.
[0072] Method for introducing carboxyl groups and / or dicarboxylic anhydride groups into copolymers: The method for introducing a carboxyl group and / or a dicarboxylic anhydride group into the copolymer according to the present invention is not particularly limited. Carboxyl groups and / or dicarboxylic anhydride groups can be introduced by various methods within the scope of the present invention. Examples of methods for introducing a carboxyl group and / or a dicarboxylic anhydride group include a method of directly copolymerizing a comonomer having a carboxyl group and / or a dicarboxylic anhydride group, and a method of copolymerizing another monomer and then introducing a carboxyl group and / or a dicarboxylic anhydride group by modification.
[0073] Methods for introducing a carboxyl group and / or a dicarboxylic anhydride group by modification include, for example, when introducing a carboxylic acid, a method in which an acrylic ester is copolymerized and then hydrolyzed to convert it to a carboxylic acid, and a method in which t-butyl acrylate is copolymerized and then thermally decomposed to convert it to a carboxylic acid.
[0074] As an additive for promoting the reaction during the hydrolysis or thermal decomposition, a conventionally known acid-base catalyst may be used. The acid-base catalyst is not particularly limited, but may be, for example, hydroxides of alkali metals or alkaline earth metals such as sodium hydroxide, potassium hydroxide, or lithium hydroxide, alkali metals such as sodium hydrogencarbonate or sodium carbonate, carbonates of alkaline earth metals, solid acids such as montmorillonite, inorganic acids such as hydrochloric acid, nitric acid, or sulfuric acid, or organic acids such as formic acid, acetic acid, benzoic acid, citric acid, paratoluenesulfonic acid, trifluoroacetic acid, or trifluoromethanesulfonic acid. From the viewpoints of reaction promotion effect, cost, equipment corrosivity, etc., sodium hydroxide, potassium hydroxide, sodium carbonate, paratoluenesulfonic acid, or trifluoroacetic acid is preferred, and paratoluenesulfonic acid or trifluoroacetic acid is more preferred.
[0075] The temperature at which the ethylene and / or C3-20 α-olefin / unsaturated carboxylic acid ester copolymer is heated may be any temperature at which the ester becomes a carboxylic acid, and if the heating temperature is too low, the ester is not converted to a carboxylic acid, whereas if the heating temperature is too high, decarbonylation and decomposition of the copolymer proceeds. Therefore, the heating temperature in the present invention is preferably in the range of 80°C to 350°C, more preferably 100°C to 340°C, even more preferably 150°C to 330°C, and even more preferably 200°C to 320°C.
[0076] The reaction time varies depending on the heating temperature, the reactivity of the ester group portion, etc., but is usually 1 minute to 50 hours, more preferably 2 minutes to 30 hours, even more preferably 2 minutes to 10 hours, still more preferably 2 minutes to 3 hours, and particularly preferably 3 minutes to 2 hours.
[0077] In the above steps, the reaction atmosphere is not particularly limited, but it is generally preferred to carry out the steps under a flow of inert gas, such as nitrogen, argon, or carbon dioxide, and a small amount of oxygen or air may be mixed in.
[0078] The reactor used in the above step is not particularly limited, and any method can be used as long as it can substantially uniformly stir the copolymer. A glass vessel or an autoclave (AC) equipped with a stirrer may be used, or any conventionally known kneading machine such as a Brabender plastograph, a single-screw or twin-screw extruder, a high-intensity screw-type kneader, a Banbury mixer, a kneader, or a roll may be used.
[0079] 3. Polyamide resin composition The polyamide resin composition of the present invention is a composition containing the above polyamide resin (I) and carboxylic acid-containing resin (II). The polyamide resin composition of the present invention can be composed of the above two components, but in order to introduce other physical properties, resins other than the above polyamide resin (I) and carboxylic acid-containing resin (II) can be blended within the scope of the present invention. Examples of such resins include polyolefin resins such as high molecular weight polyethylene, homopolymers of ethylene alone, ethylene-α-olefin copolymers, and polypropylene. The resins that can be blended are preferably polymers obtained by polymerizing monomers consisting of hydrocarbons that may contain oxygen atoms and / or nitrogen atoms in some cases. The amount of these resins to be blended is not particularly limited as long as it does not impair the impact resistance exhibited by the polyamide resin composition of the present invention, but is preferably in the range of 0 to 100 parts by weight relative to 100 parts by weight of the total of the above polyamide resin (I) and carboxylic acid-containing resin (II).
[0080] Furthermore, the resin composition of the present invention may contain additives such as conventionally known antioxidants, ultraviolet absorbers, lubricants, antistatic agents, colorants, pigments, crosslinking agents, foaming agents, nucleating agents, conductive materials, and fillers, within the scope of the present invention. Those skilled in the art can use appropriate amounts of these additives.
[0081] The polyamide resin composition of the present invention can be produced by mixing the above-mentioned components in the above-mentioned mixing ratio in any order, and kneading and granulating them using a normal kneading machine such as a single screw extruder, a twin screw extruder, a super mixer, a Henschel mixer, a Banbury mixer, a roll mixer, a Brabender plastograph, a kneader, etc. In this case, it is preferable to select a kneading and granulating method that can achieve good dispersion of each component, and kneading and granulating them using a twin screw extruder is particularly preferable from the viewpoint of economy, etc. As for the kneading machine, multiple machines using different kneading methods may be used for multi-stage kneading.
[0082] 4. Molded products One aspect of the present invention is a molded product using the polyamide resin composition. The polyamide resin composition of the present invention has high impact resistance, and is therefore effective for various applications requiring physical strength even in low-temperature environments, such as spoilers, air intake ducts, intake manifolds, resonators, fuel tanks, fuel filler tubes, fuel delivery pipes, and other automobile parts such as various hoses, tubes, and tanks, machine parts such as power tool housings and pipes, as well as electrical and electronic parts, household and office supplies, building material-related parts, and furniture parts. EXAMPLES
[0083] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. The physical properties in the examples and comparative examples were measured and evaluated by the methods shown below. In the tables, "no data" means that no measurement was performed, and "not detected" means that the value was below the detection limit.
[0084] (1) Melt flow rate (MFR) The MFR was measured in accordance with Table 1-Condition 7 of JIS K-7210 (1999) at a temperature of 190°C and a load of 21.18N.
[0085] (2) Cold and shock resistance 1) How to prepare test samples Melt blend pellets of polyamide and various modifiers were used to prepare JIS 1A test pieces by injection molding. The center of the obtained JIS 1A test piece was punched out to obtain a rectangular column with a length of 80 mm, width of 10 mm, and thickness of 4 mm. This rectangular column was vacuum dried in a vacuum dryer at 100°C for 48 hours. After that, in accordance with JIS K 7111-1, a notch was made in the center in the longitudinal direction so that the remaining width was 8 mm, and a test sample was prepared.
[0086] 2) Test method The above test pieces were stored in a freezer at -40°C for 1 hour, and then a Charpy impact test was performed in accordance with JIS K 7111-1 and an Izod impact test was performed in accordance with JIS K 7110.
[0087] (3) Absolute value of complex elastic modulus G * = Phase angle δ at 0.1 MPa (G * = 0.1MPa measurement) 1) Sample preparation and measurement The sample was placed in a 1.0 mm thick mold for hot pressing, preheated in a hot press machine with a surface temperature of 180°C for 5 minutes, and then repeatedly pressurized and depressurized to remove residual gas in the molten resin. The sample was then pressed at 4.9 MPa and held for 5 minutes. The sample was then transferred to a press machine with a surface temperature of 25°C and cooled by holding at a pressure of 4.9 MPa for 3 minutes to produce a pressed plate made of a sample with a thickness of approximately 1.0 mm. The pressed plate made of the sample was processed into a circular shape with a diameter of 25 mm to prepare a sample. The dynamic viscoelasticity was measured under the following conditions in a nitrogen atmosphere using an ARES type rotational rheometer manufactured by Rheometrics Co., Ltd. as a measuring device for dynamic viscoelastic properties. Plate: φ25mm (diameter) parallel plate ·Temperature: 160℃ Distortion: 10% Measurement angular frequency range: 1.0×10 -2 ~1.0×10 2 rad / s Measurement interval: 5 points / decade Absolute value of complex elastic modulus G * Common logarithm logG of (Pa) *Plot the phase angle δ against logG * = 5.0, the value of δ (degrees) at the point * = 0.1MPa). * If there is no point corresponding to =5.0, logG * Using two points around =5.0, logG * The δ value at logG = 5.0 was calculated by linear interpolation. * <5, logG * Using the three largest values, we plot logG on a quadratic curve. * The δ value at =5.0 was extrapolated.
[0088] (4) Melting point and crystallinity The melting point is indicated by the peak temperature of the endothermic curve measured by a differential scanning calorimeter (DSC). The measurement was performed using a DSC (DSC7020) manufactured by SII Nano Technology Co., Ltd. under the following measurement conditions. Approximately 5.0 mg of the sample was packed into an aluminum pan, heated to 200°C at 10°C / min, held at 200°C for 5 minutes, and then cooled to 30°C at 10°C / min. After holding at 30°C for 5 minutes, the sample was again heated at 10°C / min. The maximum peak temperature in the absorption curve was taken as the melting point Tm, and the heat of fusion (ΔH) was calculated from the area of the melting endothermic peak. The degree of crystallinity (%) was calculated by dividing the heat of fusion by the heat of fusion of perfect crystals of high density polyethylene (HDPE), 293 J / g.
[0089] (5) Method for measuring structural units derived from carboxyl and / or dicarboxylic anhydride monomers and the number of branches per 1,000 carbons The structural units derived from carboxyl and / or dicarboxylic anhydride monomers in the copolymer and the number of branches per 1,000 carbons are 13 It can be determined using C-NMR spectroscopy. 13 C-NMR was measured by the following method. 200-300 mg of sample was placed in an NMR sample tube with an inner diameter of 10 mm together with 2.4 ml of a mixed solvent of o-dichlorobenzene (C6H4Cl2) and deuterated bromide benzene (C6D5Br) (C6H4Cl2 / C6D5Br = 2 / 1 (volume ratio)) and hexamethyldisiloxane, a chemical shift standard substance, and the tube was purged with nitrogen, sealed, and heated to dissolve and prepare a homogeneous solution to be used as the NMR measurement sample. NMR measurements were performed at 120°C using an AV400M NMR instrument from Bruker Japan equipped with a 10 mmφ cryoprobe. 13 C-NMR was measured using the inverse gate decoupling method with a sample temperature of 120°C, a pulse angle of 90°, a pulse interval of 51.5 seconds, and an accumulation number of 512 or more. The chemical shifts are those of hexamethyldisiloxane. 13 The C signal was set at 1.98 ppm, and the other 13 The chemical shifts of the C signals were based on this.
[0090] 1) Sample pretreatment When the sample contained a carboxylate group, the sample was subjected to an acid treatment to convert the carboxylate group to a carboxyl group before measurement. When the sample contained a carboxyl group, an esterification treatment such as methyl esterification using diazomethane or trimethylsilyl (TMS) diazomethane was appropriately performed.
[0091] 2) Calculation of structural units derived from monomers having a carboxy group and / or a dicarboxylic anhydride group <e tba> The quaternary carbon signal of the t-butyl acrylate group of tBA is 13 It is detected at 79.6 to 78.8 in the C-NMR spectrum. Using these signal intensities, the amount of comonomer was calculated from the following formula. Total amount of tBA (mol%) = I(tBA) × 100 / 〔I(tBA) + I(E)〕 Here, I(tBA) and I(E) are the quantities shown in the following formulas. I(tBA)=I 79.6~78.8 I(E)=(I 180.0~135.0 +I 120.0~5.0 -I(tBA) × 7) / 2
[0092] <e tba iba> The quaternary carbon signal of the t-butyl acrylate group of tBA is 13 The methylene signal of the isobutoxy group of iBA is detected at 70.5 to 69.8 ppm, and the methyl signal of the isobutoxy group is detected at 19.5 to 18.9 ppm in the C-NMR spectrum. Using these signal intensities, the amount of comonomer was calculated from the following formula. Total amount of tBA (mol%) = I(tBA) × 100 / 〔I(tBA) + I(iBA) + I(E)〕 Total amount of iBA (mol%)=I(iBA)×100 / [I(tBA)+I(iBA)+I(E)] Here, I(tBA), I(iBA), and I(E) are quantities expressed by the following formulas, respectively. I(tBA)=I 79.6~78.8 I(iBA) = (I 70.5~69.8 +I 19.5~18.9 ) / 3 I(E)=(I 180.0~135.0 +I 120.0~5.0 -I(iBA) x 7 -I(tBA) x 7) / 2
[0093] <e tba nb> The quaternary carbon signal of the t-butyl acrylate group of tBA is 13 The methine carbon signal of NB was detected at 41.9 to 41.1 ppm in the C-NMR spectrum. Using these signal intensities, the amount of comonomer was calculated from the following formula. Total amount of tBA (mol%) = I(tBA) × 100 / 〔I(tBA) + I(NB) + I(E)〕 Total amount of NB (mol%) = I(NB) × 100 / 〔I(tBA) + I(NB) + I(E)〕 Here, I(tBA), I(NB), and I(E) are quantities expressed by the following formulas. I(tBA)=I 79.6~78.8 I(NB)=(I 41.9~41.1 ) / 2 I(E)=(I 180.0~135.0 +I 120.0~5.0 -I(NB) x 7 -I(tBA) x 7) / 2
[0094] In addition, when the structural unit amount of each monomer is indicated by "<0.1" including an inequality sign, it means that it is present as a structural unit in the multi-component copolymer, but the amount is less than 0.1 mol %, taking into account significant digits.
[0095] 3) Calculation of the number of branches per 1,000 carbon atoms When a multicomponent copolymer has branches, there are an isolated type in which the branch exists alone in the main chain, a composite type (a face-to-face type in which branches face each other via the main chain, a branched-branch type in which a branch exists within a branch chain, and a chain type). The following is an example of the structure of an ethyl branch. In the example of the facing type, R represents an alkyl group.
[0096] [ka]
[0097] The number of branches per 1,000 carbons is calculated by substituting either I(B1), I(B2), or I(B4) below into the I (branch) term in the following formula. B1 represents methyl branches, B2 represents ethyl branches, and B4 represents butyl branches. The number of methyl branches is calculated using I(B1), the number of ethyl branches using I(B2), and the number of butyl branches using I(B4). Number of branches (per 1,000 carbons) = I (branches) x 1000 / I (total) Here, I(total), I(B1), I(B2), and I(B4) are quantities expressed by the following formulas. I(total)=I 180.0~135.0 +I 120.0~5.0 I(B1)=(I 20.0~19.8 +I 33.2~33.1 +I 37.5~37.3 ) / 4 I(B2)=I 8.6~7.6 +I 11.8~10.5 I(B4)=I 14.3~13.7 -I 32.2~32.0 Here, I is the integrated intensity, and the subscripts of I indicate the range of chemical shifts. For example, I 180.0~135.0 was detected between 180.0 ppm and 135.0 ppm. 13 C The integrated intensity of the signal is shown. The attribution was based on the non-patent literature Macromolecules 1984, 17, 1756-1761 and Macromolecules 1979, 12, 41. In addition, when each branch number is indicated by "<0.1" including an inequality sign, it means that it exists as a structural unit in the multi-component copolymer, but the amount is less than 0.1 mol% considering significant figures. Also, "not detected" means below the detection limit.
[0098] <(Production Example 1): Synthesis of B-27DM / Ni Complex> The B-27DM / Ni complex was prepared according to Synthesis Example 4 described in International Publication No. 2010 / 050256, using the following 2-bis(2,6-dimethoxyphenyl)phosphano-6-pentafluorophenylphenol ligand (B-27DM). According to Example 1 of International Publication No. 2010 / 050256, a nickel complex (B-27DM / Ni) in which B-27DM and Ni(COD)2 reacted in a 1:1 ratio was synthesized using bis(1,5-cyclooctadiene)nickel(0) (referred to as Ni(COD)2). [Chemical formula]
[0099] <(Production Example 2, Production Example 3, Production Example 4): Production of Copolymer for Carboxylic Acid-Containing Resin Precursor Resin> Using the transition metal complex (B-27DM / Ni complex) prepared in Production Example 1, ethylene / t-butyl acrylate / 2-norbornene (Production Example 2), ethylene / t-butyl acrylate / i-butyl acrylate (Production Example 3), and ethylene / t-butyl acrylate copolymer (Production Example 4) were produced. The production of the copolymer was carried out with reference to Production Example 1 or Production Example 3 described in JP-A-2016-79408. Table 1 shows the production conditions and production results, such as the metal catalyst species, metal catalyst amount, trioctylaluminum (TNOA) amount, toluene amount, comonomer species, comonomer amount, ethylene partial pressure, polymerization temperature, and polymerization time, which were appropriately changed, and Table 2 shows the physical properties of the obtained copolymer. In Table 2, since the melting point of the resin satisfies the relational expression 50 < Tm < -3.74×[Z] + 130 regarding the randomness of the copolymer, it can be determined that the resins of Production Examples 2 to 4 are all resins with high randomness.
[0100]
Table 1
[0101]
Table 2
[0102] <(Production Examples 5, 6, and 7): Production of Carboxylic Acid-Containing Resins> Internal volume 1.6m 3 In a SUS316L autoclave equipped with an agitator, 100 kg of any one of the resins obtained in Production Example 2, Production Example 3, and Production Example 4, 2.0 kg of paratoluenesulfonic acid monohydrate, and 173 L of toluene were added and stirred at 105°C for 4 hours. 173 L of ion-exchanged water was added, stirred, and allowed to stand, and then the aqueous layer was extracted. Thereafter, the addition and withdrawal of ion-exchanged water was repeated until the pH of the extracted aqueous layer became 5 or higher. The remaining solution was added to a twin-screw extruder (L / D=42) equipped with a 42 mmφ vent device, and the solvent was distilled off by drawing a vacuum through the vent. Furthermore, the resin extruded continuously in the form of a strand from the die at the tip of the extruder was cooled in water and cut with a cutter to obtain resin pellets. In the IR spectrum of the obtained resin, the 850 cm -1 The disappearance of the peak near 1730 cm -1 The decrease in the peak near 1700 cm originates from the carbonyl group of the carboxylic acid (dimer). -1 An increase in the peak near the peak was observed. This confirmed the decomposition of t-Bu ester and the production of carboxylic acid, and Production Examples 5, 6, and 7 were obtained. The physical properties of the obtained precursor resins are shown in Table 3. Table 3 also shows the physical properties of AS211S, a grade of REXPEARL EAA, a commercially available carboxylic acid-containing resin (Comparative Product 1) manufactured by Japan Polyethylene Corporation.
[0103] [Table 3]
[0104] <Production of ionomers (Comparative products 2 and 3)> 1) Preparation of Na ion source A Na ion source was prepared by adding 22 g of ethylene / methacrylic acid (MAA) copolymer (Mitsui Dow Polychemicals, brand: Nucrel N1050H) and 18 g of sodium carbonate to a Labo Plastomill (Roller Mixer R60) manufactured by Toyo Seiki Co., Ltd., equipped with a small mixer with a capacity of 60 ml, and kneading the mixture at 180°C and 40 rpm for 3 minutes.
[0105] 2) Preparation of Zn ion source A Zn ion source was prepared by adding 21.8 g of ethylene / methacrylic acid (MAA) copolymer (Mitsui Dow Polychemicals, brand: Nucrel N1050H) to a Toyo Seiki Co., Ltd. Labo Plastomill: Roller Mixer R60 equipped with a 60 ml small mixer, 18 g of zinc oxide, and 0.2 g of zinc stearate, and kneading at 180 °C and 40 rpm for 3 minutes.
[0106] 3): Preparation of ionomer 40 g of the carboxylic acid-containing resin was added to a Labo Plastomill (Roller Mixer R60 type) manufactured by Toyo Seiki Co., Ltd., equipped with a small mixer with a capacity of 60 ml, and mixed and dissolved at 160°C and 40 rpm for 3 minutes. Thereafter, an ion source was added so as to achieve the desired degree of neutralization, and mixed for 5 minutes at 250°C and 40 rpm. When the IR spectrum of the obtained ionomer was checked, a peak at 1700 cm originating from the carbonyl group of the carboxylic acid (dimer) was observed. -1 The peak at 1560 cm originating from the carbonyl group of the carboxylate group decreased. -1 The physical properties of the obtained ionomer are shown in Table 4. The physical properties of commercially available ionomers (Comparative Products 4 and 5), HIM1605 and HIM1652, which are grades of HIMILAN manufactured by Dow Mitsui Polychemical Co., Ltd., are also shown in Table 4.
[0107] [Table 4]
[0108] [Examples 1 to 12 / Preparation of polyamide resin compositions] Each modifier was added to 6-nylon (manufactured by Toray Industries, Inc., product name: Amilan (registered trademark), grade: CM1017) at a predetermined weight ratio, and dry blended. This dry blend sample was melt blended using a twin-screw extruder under conditions of a die head temperature of 230°C and a screw rotation speed of 400 rpm, and the resin extruded continuously in the form of a strand from the die at the tip of the extruder was cooled in water and then cut with a cutter to obtain melt blend pellets, which are the resin compositions of Examples 1 to 12.
[0109] [Comparative Examples 1-2 / Polyamide Single Sample] A sample of 6-nylon (manufactured by Toray Industries, trade name: Amilan (registered trademark), grade: CM1017) was opened and used as is.
[0110] [Comparative Examples 3 to 38 / Preparation of Polyamide Resin Compositions] Each modifier was added to polyamide 6 (manufactured by Toray Industries, Inc., product name: Amilan (registered trademark), grade: CM1017) in a predetermined weight ratio, and melt-blended in the same manner as in Examples 1 to 12 to obtain melt-blend pellets, which are the resin compositions of Comparative Examples 3 to 38.
[0111] For the samples of Examples 1 to 12 and Comparative Examples 1 to 38 prepared as described above, test pieces were prepared by the above-mentioned method, and Izod impact tests and Charpy impact tests were carried out. The results are shown in Tables 5 and 6.
[0112] [Table 5]
[0113] [Table 6]
[0114] 4. Consideration of Examples and Comparative Examples Examples 1 to 12 are polyamide resin compositions that satisfy the constituent requirements of the present invention. * It can be seen that the cold impact strength is better than that of Comparative Examples 3, 4, 13, and 14, which contain a carboxylic acid-containing resin that does not satisfy the requirement that the phase angle δ at G = 0.1 MPa is 50 degrees to 75 degrees. * The cold impact strength was comparable to that of Comparative Examples 5 to 8 and Comparative Examples 15 to 18, which contained ionomers that satisfied the requirement that the phase angle δ at G = 0.1 MPa be 50 degrees to 75 degrees. * In Comparative Examples 9 to 12 and 19 to 22, which contain a known ionomer that does not satisfy the requirement that the phase angle δ at G = 0.1 MPa is 50 degrees to 75 degrees, the cold impact strength is lower than in Comparative Examples 5 to 8 and 15 to 18. In Comparative Examples 23 to 38, in which the compounding amount is 20 wt%, the cold impact strength is not further improved, and * Even if a carboxylic acid-containing resin is blended that satisfies the requirement that the phase angle δ at G = 0.1 MPa is 50 degrees to 75 degrees, no particular superiority is observed. * The difference in performance between the samples that do not satisfy the requirement that the phase angle δ at MPa is 50 degrees to 75 degrees at MPa = 0.1 MPa is small.
[0115] The excellent results of each of the above examples and comparisons with each of the comparative examples clearly demonstrate the significance and rationality of the configuration (matters specific to the invention) of the present invention, as well as its superiority over the prior art. [Industrial Applicability]
[0116] The polyamide resin composition using the carboxylic acid-containing resin of the present disclosure has a phase angle δ of 50 degrees to 75 degrees at G*=0.1 MPa, which is higher than that of conventional ionomers. The present invention shows the same level of cold impact resistance, and is environmentally friendly because it does not contain metal ions, and there is no risk of metal ion elution. Furthermore, since the process of producing ionomer from carboxylic acid-containing resin is not required, the cost can be reduced accordingly, and it is also economically advantageous. Therefore, the present invention can be effectively used in various molded products such as automobile parts, power tool housings, machine parts, electric and electronic parts, home and office supplies, building materials, furniture parts, packaging materials, and golf balls.< / e> < / e> < / e>
Claims
1. A polyamide resin composition comprising a polyamide resin (I) and a carboxylic acid-containing resin (II), wherein the carboxylic acid-containing resin (II) is a copolymer comprising, as essential constituent units, a structural unit (A) derived from ethylene and / or an α-olefin having 3 to 20 carbon atoms and a structural unit (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, wherein the copolymer contains 2 to 20 mol % of the structural unit (B), and the absolute value G of the complex modulus measured by a rotational rheometer is * A copolymer having a phase angle δ of 50 degrees to 75 degrees at a pressure of 0.1 MPa; The composition ratio of the polyamide resin (I) and the carboxylic acid-containing resin (II) is Polyamide resin (I): More than 80% by weight and 99.9% by weight or less Carboxylic acid-containing resin (II): 0.1% by weight or more and less than 20% by weight The polyamide resin composition according to claim 1,
2. The copolymer 13 2. The polyamide resin composition according to claim 1, wherein the number of methyl branches calculated by C-NMR is 50 or less per 1,000 carbon atoms.
3. The copolymer 13 2. The polyamide resin composition according to claim 1, wherein the number of methyl branches calculated by C-NMR is 5 or less per 1,000 carbon atoms.
4. The polyamide resin composition according to any one of claims 1 to 3, wherein the structural unit (A) is a structural unit derived from ethylene.
Citation Information
Patent Citations
Switching device
JP1980041659A
Polyamide resin composition
JP1987250053A
Thermoplastic resin composition
JP1987275157A
Impact-resistant polyamide resin composition
JP1988278964A
Composition for blow-molding
JP2007204674A